One-Pot Synthesis of Dicarbazolyl(aryl)methanols Based on α-Keto Acids - Cai, Jun-Xian; Chen, Peng; Li, Jian-Ye; Du, Hongying; Jiang, Yi-Jun (Synlett, 2024)
In this work, carbazoles, one of the most important types of nitrogenous compounds, were used as substrates to synthesize dicarbazolyl(aryl)methanols in moderate to excellent yields (up to 95%). This simple and efficient strategy can regioselectively form an sp3 quaternary carbon with two large sterically hindered carbazole rings, one benzene ring, and an active hydroxy group in a one-pot reaction. The resulting triarylmethanes are all new products, and have high potential as building blocks for medicinal chemistry or materials science.
Keywords: one-pot reaction; carbazoles; keto acids; triarylmethanes; dicarbazolylmethanols